(untitled) (Palimpsesto, 2025)
In this work, we will focus on a reflective insight from the experience of being both a sister and caregiver of a person with disabilities, and an activist, researcher, and teacher on issues related to inclusive education in Argentina. Specifically, scenes related to the author and her brother with disability playing will be selected and analyzed from a critical and social perspective of disability.